Phase relations in peridotitic and pyroxenitic rocks in the model systems CMASH and NCMASH - Schmädicke, Esther (Journal of Petrology, 2000)
Alpine-type peridotites and associated pyroxenites are found as lenses in the continental crust in many different orogens. The reconstruction of the pressure-temperature (P-T) evolution of these rocks is, however, difficult or even impossible. With geothermobarometry, usually one point on the overall P-T path can be obtained. To use the different mineral assemblages observed in ultramafic rocks as P-T indicators, quantitative P-T phase diagrams are required. This study presents new calculated phase diagrams for peridotitic and pyroxenitic rocks in the model systems CaO-MgO-Al2O3-SiO2-H2O (CMASH) and Na2O-CaO-MgO-Al2O3-SiO2-H2O (NCMASH), which include the respective solid solutions as continuous exchange vectors. These phase diagrams represent applicable petrogenetic grids for peridotite and pyroxenite. On the basis of these general petrogenetic grids, phase diagrams for particular peridotite and pyroxenite bulk compositions are constructed. In an example of pyroxenite from the Shackleton Range, Antarctica, the different observed mineral assemblages are reflected by the phase diagrams. For these rocks, a high-pressure metamorphic stage around 18 kbar and an anticlockwise P-T evolution, not recognized previously, can be inferred.
UnivIS-Import:2017-03-24:Pub.2000.nat.dgeo.IGM.profes_1.phaser_26
Keywords: Antarctic; High-pressure metamorphism; Peridotite; Phase diagrams; Pyroxenite